Association of Preadmission Metformin Use and Prognosis in Patients With Sepsis and Diabetes Mellitus: A Systematic Review and Meta-Analysis - Li, Yuanzhe; Zhao, Huayan; Guo, Yalin; Duan, Yongtao; Guo, Yanjun; Ding, Xianfei (Frontiers in Endocrinology, 2021)
Background and Aim: A growing body of evidence suggests that the preadmission metformin use could decrease the mortality of septic patients with diabetes mellitus (DM); whereas the findings are contriversial yet. Therefore, this meta-analysis on available studies to confirm the relationship between preadmission metformin use and mortality in patients with sepsis and DM. Methods: A comprehensive search of PubMed, Embase, and the Cochrane Library for studies published before August 8, 2021 was performed. Observational studies assessing the correlation between metformin and mortality in patients with sepsis and DM were considered eligible studies. We used the Newcastle–Ottawa Scale to assess the outcome quality of each included article. Furthermore, the odds ratios (ORs) and 95% confidence intervals (CIs) were analyzed by the inverse variance method with random effects modeling. Results: Eleven articles including 8195 patients were analyzed in this meta-analysis. All the included articles were scored as low risk of bias. Our results show that preadmission metformin use had a lower mortality rate (OR, 0.74; 95% CIs, 0.62-0.88, P<0.01) in patients with sepsis and DM. Surprisingly, preadmission metformin use has no statistically inscrease the levels of serum creatinine (WMD, 0.36; 95% CIs, -0.03-0.75; P=0.84) and lactic acid (WMD, -0.16; 95% CIs, -0.49-0.18; P=0.07) compared with the non-metformin use. Conclusions: This meta-analysis shows that preadmission metformin use could reduce mortality and not increase serum creatinine and lactic acid in adults patients with sepsis and DM. these data suggests that the potential efficacy of metformin can be assessed in future high original clinical studies.